The concept of the teacher as a reflective professional and its use in english language teacher education in Brasil - Greggio, Saionara (2009)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente, Florianópolis, 2009